10 Macrophage-derived wnts are required for scar-free regeneration of the neonatal mouse myocardium. (1st April 1997) - RFP, Castellan; M, Thompson; DYH, Soong; KJ, Mylonas; A, Thomson; CM, Moran; RN, Kitsis; JW, Pollard; GA, Gray
Abstract : Objective: In contrast to the adult, neonatal mice regenerate their myocardium following injury, at least during the first week after birth. 1 Macrophages (M&x0424;) contribute to vessel formation and scar removal following neonatal myocardial infarction (MI) 2 . In the kidney 3 liver 4, 7 and gut 5 M&x0424;-derived WNTs are required for scar free regeneration following injury. Secretion of WNTs is dependent on acylation by Porcupine (PORCN). In the present study it was hypothesised that neonatal cardiac regeneration would be impaired in mice with Csf1r-Cre driven M&x0424; specific Porcn deletion. 5 Methods: Csf1r-EGFP(MacGreen), Porcn fl/ Csf1r Cre-ve and Porcn fl /Csf1r Cre+ve mice underwent coronary artery ligation at post-natal day 1 (P1). Functional loss 1 day after MI, and recovery by P21 were assessed by high-resolution ultrasound. Heart sections were stained with isolectin B4 (vessel density) and picrosirius res (fibrosis). Myocardial gene expression was determined by PCR array in wild-type (WT) mice after injury. Results: At day 1 and day 7 post-MI, Csf1r-expressing cells accumulated within the injured myocardium, consistent with a role in regeneration. 2 At day 1 post-MI, fractional area change (FAC) decreased from 40.9% ± 1.6 to 18.0% ± 2.4% (p<0.0001) and from 41.0% ± 1.3 to 16.5% ± 2.7% (p<0.0001) in Porcn fl/ Csf1r Cre-ve and Porcnfl/Csf1rCre-ve mice respectively. By 21 days after MI, FAC had recovered to 47.4% ± 2.5% (p<0.0001) in Porcn fl/ Csf1r Cre-ve and 45.8% ± 1.9% (p<0.0001) in Porcn fl/ Csf1r Cre-ve littermates. Coronary vascularisation was restored in the infarct area by 21 days in both lines, but interstitial fibrosis was significantly higher in Porcn fl/ Csf1r Cre-ve (6.0 ± 0.9% LV) compared to Porcn fl/ Csf1r Cre-ve (3.8 ± 0.5% LV, p<0.05). In WT neonatal hearts, MI increased the expression of Wnt5b and Fzd2, genes associated with regulation of fibrosis. 8 Conclusion: M&x0424;-derived WNTs are not required for re-vascularisation or restoration of myocardial function after neonatal myocardial injury, but are necessary for scar removal during regeneration. References: Porrello et al . PNAS 2013;110 :p187–92. Aurora et al . JCI 2014;124 :p1382–92. Lin et al . PNAS 2010;107 :p4194–99. Boulter et al . Nat Med 2012;18 :572–9. Saha et al . Nat Com 2016;7 :1–16. Derlindati et al . PLoS ONE 2015;10 :1–17. Irvine et al . Fibrogenesis Tissue Repair 2015;8 :19–32. Laeremans et al . Cardiovascular Research 2010;87 :514–523.